PKM Penerapan Sistem Informasi Kebencanaan Desa Kukuh dalam Mewujudkan Desa Digital Tangguh dan Siaga Bencana - Pandawana, I Dewa Gede Agung; I Gede Yudha Partama; Dewa Gede Agung Gana Kumara; I Nyoman Widhi Adnyana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Kukuh Village in Kerambitan District has a hilly topography, large rivers, and high rainfall, which makes the area prone to disasters, especially floods, landslides, and extreme weather. In order to overcome these problems, the Community Service Program (PKM) aims to: 1) create a Disaster Prone Map, Safe Zone Map, Evacuation Route Map, and Temporary Refuge Map; 2) build an informative, interactive, effective, and efficient village disaster information system based on digital technology; 3) organize counseling and training on disaster management to improve community preparedness; 4) provide disaster support tools. The implementation of the community partnership program uses the Knowledge Transfer approach through counseling and training, Technology Transfer through participatory mapping, and Diffusion of Science and Technology through the creation of the SIKADEK application (Kukuh Village Disaster Information System). The PKM results include a Disaster Map that is integrated with the SIKADEK application as a Disaster WebGIS feature, including weather information, distribution of disaster-prone areas, disaster history, and Balinese lunar calendar information (Sasih). Training and counseling increased the capacity of Pokdarwis with knowledge about disaster-prone locations, safe zones, rallying points, evacuation routes, utilization of disaster features in the SIKADEK application, as well as knowledge about disasters, vulnerable areas, management, and disaster mitigation. In addition, disaster support facilities such as signs, water rescue packages, and first aid packages have been fulfilled through this activity.